2017
DOI: 10.1038/cdd.2017.96
|View full text |Cite
|
Sign up to set email alerts
|

p53-mediated suppression of BiP triggers BIK-induced apoptosis during prolonged endoplasmic reticulum stress

Abstract: Physiological and pathological conditions that affect the folding capacity of the endoplasmic reticulum (ER) provoke ER stress and trigger the unfolded protein response (UPR). The UPR aims to either restore the balance between newly synthesized and misfolded proteins or if the damage is severe, to trigger cell death. However, the molecular events underlying the switch between repair and cell death are not well understood. The ER-resident chaperone BiP governs the UPR by sensing misfolded proteins and thereby r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 58 publications
4
39
0
1
Order By: Relevance
“…Consistent with these above reports, we identify that lncRNA MEG3 could directly bind to and regulate p53 expression in NMVMs by RIP and Western blot assays, but which were not entirely the same as Wu.et al research . Previous studies have found that p53 could also regulate the levels of GRP78, CHOP and Bax, which exerted key roles in the process of ERS, leading to apoptosis . However, the regulatory mechanism between p53 and ERS remains unclear.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with these above reports, we identify that lncRNA MEG3 could directly bind to and regulate p53 expression in NMVMs by RIP and Western blot assays, but which were not entirely the same as Wu.et al research . Previous studies have found that p53 could also regulate the levels of GRP78, CHOP and Bax, which exerted key roles in the process of ERS, leading to apoptosis . However, the regulatory mechanism between p53 and ERS remains unclear.…”
Section: Discussionsupporting
confidence: 90%
“…28 Previous studies have found that p53 could also regulate the levels of GRP78, CHOP and Bax, which exerted key roles in the process of ERS, leading to apoptosis. [34][35][36] However, the regulatory mechanism between p53 and ERS remains unclear. Studies indicate that NF-κB signalling was reported to be a vital in regulating ERS-and p53-related myocardial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the notion that a pro-apoptotic response is more likely if the cell fails to arrest in G2 and to restore the ER homeostasis, in a similar fashion as the p53fl-dependent apoptosis is triggered when cells fail to arrest in G1 following genotoxic stress [20,25]. Interestingly, induction of apoptosis by p53 during ER stress relies, at least in part, on the suppression of BiP synthesis (Table 1) [98]. In addition to its chaperoning activity, BiP binds several partners, including the inducers of the UPR axis, that together control cell growth and protect against stress-induced apoptosis [99][100][101][102][103][104][105][106].…”
Section: Induction Of Apoptosissupporting
confidence: 74%
“…Accordingly, BiP is upregulated in various cancers, including brain, prostate, head and neck and melanoma [41,[107][108][109][110]. Though the molecular mechanisms remain largely unknown, BiP's mRNA interaction with p53 resulted in inhibition of BiP protein synthesis and therefore less interaction between BiP and Bcl-2-interacting killer (BIK), a pro-apoptotic member of the Bcl-2 family [98,106]. Remarkably, the p53-dependent drop in BiP/BIK association only occurred during ER stress, implying that stress conditions are also key in controlling the BiP-BIK interaction and cell fate decisions [98].…”
Section: Induction Of Apoptosismentioning
confidence: 99%
“…Previous studies have reported the association between P53 and UPR in malignancies. However, the outcomes appear to be tissue‐specific, since it was shown that the endoplasmic reticulum stress stimulates P53 expression through nuclear factor‐κB (NF‐κB) activation, while others have demonstrated the opposite effects in different experimental systems . Several studies have shown the correlation of endoplasmic reticulum stress and UPR to endothelial dysfunction in both animal and cellular models .…”
Section: Discussionmentioning
confidence: 99%